A single injection of pregabalin induces short- and long-term beneficial effects on fear memory and anxiety-like behavior in rats with experimental type-1 diabetes mellitus - de Lima Silva, Alvaro Henrique Bernardo; Radulski, Debora Rasec; Pereira, Gabriela Saidel; Acco, Alexandra; Zanoveli, Janaina Menezes (Metabolic brain disease, 2022)
Anxiety Disorders and Posttraumatic Stress Disorders (PTSD) associated with type-1 diabetes mellitus (T1DM) are increasingly common comorbidities and the treatment is quite challenging. In that sense, evidence indicates that the anticonvulsant pregabalin is highly effective in treating severe cases of anxiety, as well as PTSD and diabetic neuropathic pain which is also very prevalent in T1DM. Herein, the short- and long-term effects of a single injection of pregabalin on the acquisition of a fear extinction memory and parameters of anxiety in induced-T1DM animals were investigated. For that, we used the contextual fear conditioning (CFC) and elevated plus maze paradigms, respectively. A putative antioxidant activity was also evaluated. Our findings demonstrated that induced-T1DM animals presented greater expression of fear memory, difficulty in extinguishing this fear memory, associated with a more pronounced anxiety-like response. Pregabalin was able to induce a short and long-lasting effect by facilitating the acquisition of the fear extinction memory and inducing a later anxiolytic-like effect. Also, the increased lipid peroxidation levels in the hippocampus and prefrontal cortex of induced-T1DM rats were reduced after pregabalin injection, while the decreased levels of reduced glutathione were increased in the hippocampus. Despite the need for more studies to understand the mechanism of action of pregabalin under these conditions, our data demonstrate for the first time that a single injection of pregabalin in a specific time window was able to improve behavioral parameters in addition to inducing neuroprotective effect. Thus, pregabalin has potential worth exploring for the treatment of PTSD and/or Anxiety associated with T1DM.